Synthesis and evaluation of a high precision 3D-printed Ti6Al4V compliant parallel manipulator - Wang, Pan (2018)
A novel 3D printed compliant parallel manipulator (CPM) with θX − θX − Z motions is presented in this paper. This CPM is synthesized using the beam-based method, a new structural optimization approach, to achieve optimized stiffness properties with targeted dynamic behavior. The CPM performs high non-actuating stiffness based on the predicted stiffness ratios of about 3600 for translations and 570 for rotations, while the dynamic response is fast with the targeted first resonant mode of 100Hz. A prototype of the synthesized CPM is fabricated using the electron beam melting (EBM) technology with Ti6Al4V material. Driven by three voice-coil (VC) motors, the CPM demonstrated a positioning resolution of 50nm along the Z axis and an angular resolution of ~0.3 "about the X and Y axes, the positioning accuracy is also good with the measured values of ±25.2nm and ±0.17" for the translation and rotations respectively. Experimental investigation also shows that this large workspace CPM has a first resonant mode of 98Hz and the stiffness behavior matches the prediction with the highest deviation of 11.2%. Most importantly, the full workspace of 10° × 10° × 7mm of the proposed CPM can be achieved, that demonstrates 3D printed compliant mechanisms can perform large elastic deformation. The obtained results show that CPMs printed by EBM technology have predictable mechanical characteristics and are applicable in precise positioning systems.